Issues of Corrective Feedback in Second Language Acquisition - Ji Hyun Kim (Studies in Applied Linguistics & TESOL, 2004)
For decades now, questions about the role of corrective feedback in second language acquisition (SLA) have been hotly debated, spawning a great deal of theoretical and empirical research. Although the facilitative role of corrective feedback in SLA has received some empirical support, the claims regarding its impact on SLA have yet to be fully or decisively substantiated. In order to move this line of research forward, it is important to examine the issues arising in the SLA literature. To this end, this paper aims to review and discuss the literature throwing light on three major issues: (1) learners’ noticing of feedback, (2) potential mismatches between teachers’ intentions and learners’ interpretations, and (3) the role of different types of implicit corrective feedback.